Dual Targeting to Overcome Current Challenges in Multiple Myeloma CAR T-Cell Treatment - van der Schans, Jort J.; van de Donk, Niels W. C. J.; Mutis, Tuna (Frontiers in Oncology, 2020)
In the era of highly promising novel targeted-immunotherapy strategies for multiple myeloma (MM), the first series of clinical trials with CAR T-cells targeting the plasma cell-specific B-cell maturation antigen (BCMA) have shown excellent response rates. In the long-term, however, MM appears to escape the therapy likely due to initial low and heterogeneous expression or downregulation of BCMA expression. Several other molecules targeted by CAR T-cells in MM are expressed at high levels on MM cells, but many of these attractive targets are also expressed on various, sometimes vital non-malignant cells, posing major risks for on-target, off-tumor side effects. CAR T-cell therapy for MM therefore faces two urgent challenges: (i) improving the efficacy of BCMA CAR T-cells and (ii) establishing a MM-selectivity even when CAR T-cells are directed against not entirely MM-specific target antigens. In this review, we will outline the current attempts to tackle these challenges, with a specific focus on how dual CAR targeting might be applied to tackle both issues.